WNT16 from decidual stromal cells orchestrates M2 macrophage polarization via β-catenin signaling and chromatin remodeling at the maternal-fetal interface - Chang, Lingyu; Guo, Jiani; Xue, Xi; Yan, Yang; Li, Xinyi; Zhao, Weijie; Sun, Xiaoli; Chen, Jiajia; Du, Meirong (Frontiers in Immunology, 2025)
BackgroundPregnancy maintenance requires precise immunoregulation at the maternal-fetal interface, where M2-polarized decidual macrophages (dMφ) support immune tolerance. While canonical WNT signaling is reported to regulate macrophage polarization, its specific function within the decidual immune microenvironment remains insufficiently understood. Moreover, whether individual ligands such as WNT16 can epigenetically reprogram decidual macrophage responses has yet to be elucidated.MethodsEndometrial stromal cells (ESCs) from non-pregnant women and decidual stromal cells (DSCs) from normal pregnancies (NP) and recurrent spontaneous abortion (RSA) were accessed for WNT16 expression by RT-qPCR, ELISA and immunohistochemistry. The effects of WNT16 on macrophages were examined using RNA-seq and flow cytometry in peripheral monocyte-derived macrophages (pMo) and dMφ treated with recombinant WNT16 or DSC-conditioned medium. Canonical WNT pathway was evaluated by luciferase reporter assays, western blotting (WB) and immunofluorescence. Integrated ATAC-seq and RNA-seq analyses were employed to detect the epigenomic alterations downstream of the WNT/β-catenin pathway, in which the function of DIXDC1 was further evaluated by siRNA knockdown.ResultsWe found that WNT16 was highly expressed in DSCs from NP women compared with ESCs and DSCs from RSA patients. WNT16 selectively promoted M2-like polarization of pMo without altering NK or T cell phenotypes. Mechanistically, WNT16 activated the WNT/β-catenin pathway in dMφ and enhanced chromatin accessibility at M2-associated loci. Integrated multi-omics analysis suggested a MYC-DIXDC1 regulatory axis downstream of WNT16. Functional DIXDC1 knockdown confirmed its role in β-catenin activation and macrophage polarization, indicating that this axis may contribute to WNT16-mediated M2 programming.ConclusionsDSC-derived WNT16 promotes M2 polarization in decidual macrophages, which involves the activation of the WNT/β-catenin pathway and the feedback of a MYC–DIXDC1 regulatory axis. Our findings reveal an essential immunoregulatory and epigenetic mechanism critical for successful pregnancy.